Effect of breed differences on semen qualities in adult male chickens in Nigeria - Oyeleye, Olubisi Oluseun; Adelani Abayomi Adeoye; Thomas Ayodele Fatoba (Universitas Airlangga, 2025)
Efficient reproduction is paramount for the sustainability and profitability of poultry enterprises. This study examined the influence of breed on semen quality traits in four chicken breeds commonly found in Nigeria, namely White Yaffa, Noiler, Yoruba ecotype and Fulani ecotype. A total of 40-day-old male chicks were used in the experiment, with 10 birds per breed. The birds were raised to 26 weeks before semen was collected. Mature cocks from each breed were subjected to semen collection and evaluation, with emphasis on both qualitative and quantitative parameters such as semen volume, color, viscosity, odor, motility, viability, and morphological characteristics. The findings revealed significant differences among the breeds studied (p <0.05). Noiler cocks recorded the highest semen volume (0.52 ± 0.04 mL) while the indigenous Yoruba ecotype produced the lowest semen volume (0.31 ± 0.01 mL). White Yaffa performed best with the highest fast progressive motility (80.33%), followed by Noiler, Fulani, and lastly Yoruba respectively at p <0.05. The sperm counts showed that Fulani had the highest concentration (1.33×10⁹/mL), followed by White Yaffa (1.23×109/mL) and Yoruba (1.11×109/mL). Noiler, in spite of its large semen volume, had the lowest sperm concentration (0.67×109/mL). Despite this variation, all breeds displayed normal semen color, viscosity, and odor, reflecting general semen viability across the groups. In conclusion, this study highlights the importance of breed as a determining factor in semen quality of male chickens. The findings from this study provides useful insight for poultry breeders, researchers and farmers in selecting suitable breeds for breeding programs.